2012
DOI: 10.1371/journal.pone.0041773
|View full text |Cite
|
Sign up to set email alerts
|

β,β-Dimethylacrylshikonin Induces Mitochondria Dependent Apoptosis through ERK Pathway in Human Gastric Cancer SGC-7901 Cells

Abstract: β,β-Dimethylacrylshikonin, one of the active components in the root extracts of Lithospermum erythrorhizon, posses antitumor activity. In this study, we discussed the molecular mechanisms of β,β-dimethylacrylshikonin in the apoptosis of SGC-7901 cells. β,β-Dimethylacrylshikonin reduced the cell viability of SGC-7901 cells in a dose- and time-dependent manner and induced cell apoptosis. β,β-Dimethylacrylshikonin treatment in SGC-7901 cells down-regulated the expression of XIAP, cIAP-2, and Bcl-2 and up-regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
2
24
0
1
Order By: Relevance
“…EGF stimulation caused a transient activation of ERK1/2, peaking at 15 min and reducing back to basal levels after 40 min, and induced cell proliferation in PC12 cells, while NGF stimulated sustained activation of A B C D ERK1/2 after 15-180 min, which resulted in the differentiation of cells (20). Previously, β,β-dimethylacrylshikonin induced mitochondria-dependent apoptosis through the ERK pathway in human gastric cancer SGC-7901 cells (21). Shen et al (21) suggested that sustained ERK activation induces apoptosis.…”
Section: A B Cmentioning
confidence: 94%
See 2 more Smart Citations
“…EGF stimulation caused a transient activation of ERK1/2, peaking at 15 min and reducing back to basal levels after 40 min, and induced cell proliferation in PC12 cells, while NGF stimulated sustained activation of A B C D ERK1/2 after 15-180 min, which resulted in the differentiation of cells (20). Previously, β,β-dimethylacrylshikonin induced mitochondria-dependent apoptosis through the ERK pathway in human gastric cancer SGC-7901 cells (21). Shen et al (21) suggested that sustained ERK activation induces apoptosis.…”
Section: A B Cmentioning
confidence: 94%
“…Previously, β,β-dimethylacrylshikonin induced mitochondria-dependent apoptosis through the ERK pathway in human gastric cancer SGC-7901 cells (21). Shen et al (21) suggested that sustained ERK activation induces apoptosis. In this study, a specific inhibitor of MEK blocked β,β-dimethylacrylshikonin-induced ERK activation and apoptosis in SGC-7901 cells (21).…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng Y et al also found that acetylshikonin led to cell apoptosis in human gastric carcinoma cell line SGC-7901 via elevation of Bax /Bcl-2 ratio (Zeng et al, 2009). Recently, we reported that β,β-dimethylacrylshikonin induced mitochondria-dependent apoptosis via ERK1/2 pathway in human gastric cancer SGC-7901 cells (Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 72%
“…The translocalization of apoptotic proteins from the cytoplasm to the mitochondria membrane leads to cytochrome c release and second mitochondria-derived activator of caspases by a loss of mitochondrial membrane potential (Shimizu et al, 1999). Our previous findings have demonstrated that β,β-dimethylacrylshikonin induces apoptosis via mitochondria pathway in SGC-7901 cells (Shen et al, 2012). In the present study, we showed that MBS down-regulated the expression of Bcl-2 and up-regulated the expression of Bak, and caused the loss of mitochondrial membrane potential in SW620 cells, consistent with activation of the mitochondria-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 96%